Proceedings of the Proceedings of the 1st International Conference on Finance Economics and Business, ICOFEB 2018, 12-13 Novemb 2019
DOI: 10.4108/eai.12-11-2018.2288771
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Personal Value, Moral Philosophy, and Organizational Ethical Culture on Auditor Action and Acceptance for Dysfunctional Behavior

Abstract: Objectives of this research are to investigate the effect of organizational ethical culture, personal values, and moral philosophy on auditor actions and acceptance for dysfunctional behaviour. This research also seeks to investigate the effect of organizational ethical culture through personal values and moral philosophy on auditor actions and acceptance for dysfunctional behaviour and effect of personal auditor value on his moral philosophy. By using structural equation modeling technique from survey result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Accountants' personal values related to self-enhancement influence the level of acceptance to-ward dysfunctional behavior. Those who lean toward the moral philosophy of idealism rather than relativism are accountants with personal values rooted in conservatism and self-enhancement, but the accountants who incline toward relativism hold personal values aligned with openness to change (Komalasari et al, 2019).…”
Section: Personal Valuesmentioning
confidence: 99%
“…Accountants' personal values related to self-enhancement influence the level of acceptance to-ward dysfunctional behavior. Those who lean toward the moral philosophy of idealism rather than relativism are accountants with personal values rooted in conservatism and self-enhancement, but the accountants who incline toward relativism hold personal values aligned with openness to change (Komalasari et al, 2019).…”
Section: Personal Valuesmentioning
confidence: 99%
“…Ethical values are values that lead to the existence of a rule that is closely related to the existence of morals originating from culture, philosophy and religion (Hernando et al, 2018). Ethical values are defined as moral principles that distinguish between right and wrong which function as norms in behavior (Komalasari et al, 2019).…”
Section: 33ethical Valuementioning
confidence: 99%
“…Organisational ethics context factors or ethical context are characterised by a strong emphasis on ethicality (Komalasari et al 2019;Trevino, Butterfield & McCabe 1998), and as such, is a topic that has received a great deal of attention during the past 20 years (Rachele et al 2013;Rashid, Sambasivan & Johari 2003;Suh, Shim & Button 2018). Studies have shown that the organisational ethics context factors have a significant impact on employees' job satisfaction and well-being (El-Nahas, Abd-El-Salam & Shawky 2013; Raja et al 2020), and ultimately on the organisation's success (Rashid et al 2003).…”
Section: Introductionmentioning
confidence: 99%